Production Performance, Phenotypic and Carcass Quality Sensory Evaluation of Kadaknath, Rhode Island Red Chicken and their Reciprocal Crosses - Bhagora, Nikesh J.; Mishra, Ramkailash; Savaliya, Fulabhai P.; Patel, Atul B.; Lonkar , Vijay Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The performance of reciprocal crosses of Rhode Island red (RIR) and Kadaknath was studied for comparison with the performance of  purebred RIR and Kadaknath. A total of 292 birds comprising of purebred RIR and Kadaknath and reciprocal crosses were divided into  four groups, viz., 74 birds of purebred Rhode Island red (R), 70 birds of purebred Kadaknath (K); and 72 birds of Rhode Island Red x  Kadaknath (R x K) and 76 birds of Kadaknath x Rhode Island Red (K x R) as reciprocal crosses. The body weight (BW) at day-old, 4, 8, 12,  16, 20, 28, 36, and 40 weeks of age, age at first egg (AFE) and total egg number (TEN) up to 40th week of age were recorded for each  group. The phenotypic characteristics of birds and their egg quality parameters were recorded at the 40th week of age. The phenotypic  and carcass qualities were recorded at the 28th week of age for male and female birds. The results of the study indicated that the body  weight (BW), egg weight (EW), TEN, and dressed weight (DW) for purebred RIR were significantly (p
Keywords: Carcass quality; Kadaknath; Performance; Phenotype; Reciprocal crosses; Rhode Island Red